A study of pregnancy related acute kidney injury and its outcome at a tertiary care centre, civil hospital, Ahmadabad, Gujarat, India - Agrawal, Komal K.; Jain, Mahima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy related acute kidney injury (PRAKI) is acute kidney injury occurring during pregnancy, labour, delivery, and/or postpartum period. Proper management of PRAKI is challenging because (i) both maternal and fetal health must be considered and (ii) the cardiovascular and renal adaptations of pregnancy add to the complexity of diagnosis and management. A multi discipilinary team is often needed to optimize all aspects of the pregnant women’s care. Methods: To study association and contributing factors in pregnancy related Acute Kidney injury, a retrospective study of 39 cases of acute kidney injury complicating pregnancies was carried out in department of obstetrics and gynaecology, B. J. Medical college over a period of 6 months, and results were studied and analysed. Etiological-factors, associated liver pathology, coagulation abnormality, thrombocytopenia, sepsis, recovery status and fetomaternal outcome were studied and results were tabulated. AKI was analysed in terms of maximal stage of renal injury attained as per risk, injury, failure, loss of function, and end-stage renal disease (RIFLE) criteria. Results: The incidence of ARF in pregnancy was found to be 0.3%. Hypertension and its related complications were the most common causative factor. 59.5% of cases required hemodialysis and except for 6 cases (14.3%) all had complete or at least partial recovery from failure. Conclusions: AKI complicating pregnancies are not uncommon in tertiary care centres. If recognized and treated promptly, recovery is assured in majority of 85.7% of cases. Early identification and prompt management of pre-eclampsia and sepsis can prevent majority of ARF cases.